Sustainable life and social development through universally designed environment / Syazwani Abdul Kadir and Mariam Jamaludin. - Abdul Kadir, Syazwani; Jamaludin, Mariam (Universiti Teknologi MARA Cawangan Selangor, 2018)
Universally designed environment provides comfort, adaptability and flexibility that can help to reduce human life cycle impact and encourage residents’ participation in the community. With that, the purpose of this conceptual study is to explore the concept of Universal Design (UD) as a significant aspect of social sustainability, based on professional practitioners’ and scholarly views. UD implementation in built environment may cater the needs of diverse users over the changing abilities throughout lifespan. This study concludes that UD has evolved as a significant component for sustainable life and social development within the individual’s own dwelling and the community as well.